DNA-loaded targeted nanoparticles as a safe platform to produce exogenous proteins in tumor B cells - Grimaldi, Maria Cristina; Bozzer, Sara; Sjöström, Dick J.; Andersson, Linnea I.; Mollnes, Tom Eirik; Nilsson, Per H.; De Maso, Luca; Riccardi, Federico; Dal Bo, Michele; Sblattero, Daniele; Macor, Paolo (Frontiers in Immunology, 2025)
IntroductionThe functionalization of nanoparticles (NPs) with an antiCD19 targeting mechanism represents a promising approach for the selective delivery of drugs and nucleic acids into normal and tumor B cells. This strategy has the advantage of minimizing off-target effects by restricting gene delivery to the desired cell population. However, the nanoplatform must guarantee both the local production of the protein and the safety of the treatment to allow an effective therapy with reduced systemic toxicity.MethodsIn order to ensure a selective delivery of nucleic acids, we developed poly(lactic-co-glycolic acid) (PLGA)-poly(vinyl alcohol) (PVA) NPs loaded with an Enhanced Green Fluorescent Protein (EGFP)-coding plasmid and covalently coated with antiCD19 recombinant antibody as a targeting mechanism. To assess the functionality of the NPs, physicochemical characterization, safety tests, and transfection assay were employed to evaluate the NPs’ behavior in vitro and in vivo, in a human/zebrafish lymphoma xenograft model.ResultsThe results demonstrated that the PLGA-PVA nanoplatform was capable of efficiently encapsulating and releasing the payload. These nanostructures demonstrated a favorable safety profile, as evidenced by the absence of significant cell cytotoxicity, coagulation activation, complement system activation, and the slight activation of endothelial cells and leukocytes. The targeting mechanism facilitated the interaction of NPs with target cells, thereby enhancing their internalization and subsequent exogenous plasmid DNA (pDNA) translation and protein expression. In the human/zebrafish lymphoma xenograft model, no evidence of toxicity was observed, and targeted NPs demonstrated the capacity to enhance exogenous pDNA expression.ConclusionOur findings provide a rationale for the use of targeted NPs as a DNA delivery system for the local expression of therapeutic proteins.